Double blinding requirement for validity claims in cognitive-behavioral therapy intervention trials for major depressive disorder. Analysis of Hollon S, et al., Effect of cognitive therapy with antidepressant medications vs antidepressants alone on the rate of recovery in major depressive disorder: a randomized clinical trial - Berger, Douglas (F1000Res, 2015)
This paper will focus on problems in the inability to double-blind cognitive-behavioral therapy (CBT) studies for major depressive disorder (MDD), and provides an analysis of a recently published study to show how this problem can lead to faulty conclusions. A study by Hollon et al. published in JAMA Psychiatry that compared an antidepressant medication-only arm with a combined CBT/antidepressant arm concluded that the cognitive therapy/antidepressant combination enhanced the recovery rates compared with antidepressant alone, and that the magnitude of this increment nearly doubled for patients with more severe depression. We propose that for subjects with greater severity, there could have been both antidepressant efficacy as well as more hope and expectation in the group who knew they had received combined cognitive therapy/medication, leading to an erroneous conclusion of greater efficacy for the combined group. The large subject number in this study could easily lead to an erroneous finding on statistical testing as a small amount of bias in the subjects adds-up. We opine that the conclusions of unblind CBT outcome research in conditions with subjective endpoints such as MDD need to be given with great caution. The validity of CBT (and its derivatives such as dialectical behavioral therapy) for indications other than MDD is also part of a larger problem in  the inability to blind outcome studies for these interventions.